Challenges of Science Learning in the Era of Short Attention Span: Elementary School Teachers' Perspectives - Maria Adventini Leto; Leonardo Ofriayu; Stevanus Rivaldo Leto; Jefrianus Bau; Egithia Alfi Rosydiana (Experiment: Journal of Science Education, 2026)
The phenomenon of short attention spans is one of the challenges in learning Natural Sciences (IPA) in elementary schools in the digital era. Changes in student attention characteristics require teachers to implement learning strategies that are able to maintain student focus and engagement. This study aims to describe the challenges of science learning in the short attention span era based on the perspective of elementary school teachers. The research uses a quantitative approach with a descriptive survey method. The research sample consisted of 30 elementary school teachers who were selected using purposive sampling techniques. Data were collected using a Likert scale questionnaire that had been validated through expert judgment and analyzed using descriptive statistics in the form of mean, median, and standard deviation. The results showed that teachers still showed diverse perceptions in identifying the characteristics of short attention span in students (mean = 3.21; SD = 1.06) so that it is in the category of doubt. Meanwhile, the teacher stated that he agreed that digital technology and gadgets had an effect on the short attention span (mean = 3.87; SD = 1.01), this phenomenon has an impact on science learning (mean = 3.62; SD = 1.01), and is a challenge in the implementation of science learning (mean = 3.98; SD = 0.94). The indicator with the highest score was the teacher's strategy in overcoming the short attention span (mean = 4.38; SD = 0.69) which belongs to the category is very agreeable. These findings suggest that teachers view the implementation of active, interactive, and varied learning strategies as an important effort to retain students' attention. Therefore, improving teachers' competence in recognizing the characteristics of short attention spans and designing adaptive science learning is an important need in the digital era.